Content–based queries in image database - Lim, Cher Hong. (2010)
The aim of this report is to review how of the images searching through keyword and template searching. Many different types of search engine are on the World Wide Web (www) right now, but many of them are keyword searching instead of template searching. The basic working principles of the both keyword searching and template searching are to be discussed.